Low-dose dasatinib in older patients with chronic myeloid leukaemia in chronic phase (DAVLEC): a single-arm, multicentre, phase 2 trial. Issue 12 (December 2021) - Murai, Kazunori; Ureshino, Hiroshi; Kumagai, Takashi; Tanaka, Hideo; Nishiwaki, Kaichi; Wakita, Satoshi; Inokuchi, Koiti; Fukushima, Toshihiro; Yoshida, Chikashi; Uoshima, Nobuhiko; Kiguchi, Toru; Mita, Masayuki; et al.
Summary: Background: BCR-ABL1 tyrosine kinase inhibitors (TKIs) are commonly initiated in older patients with chronic myeloid leukaemia in the chronic phase at standard doses. However, because of their safety profile in this population, appropriate therapy has not been established. We aimed to investigate whether a lower than standard dose of dasatinib was an appropriate therapy for older patients with chronic myeloid leukaemia in the chronic phase. Methods: DAsatinib, Very Low-dose, for Elderly CML-CP patients (DAVLEC) was a multicentre, single-arm, phase 2 trial done in 25 Japanese hospitals. We enrolled patients older than 70 years with newly diagnosed chronic myeloid leukaemia in the chronic phase, ECOG performance status 0–2, and no previous treatment for CML other than hydroxyurea within 4 weeks. Second-generation TKI dasatinib was given orally at a starting dose of 20% of the standard dose (20 mg/day). If the treatment was assessed as optimal response at 3 months, 6 months, and 9 months and adverse events were grade 2 or better (according to the NCI Common Toxicity Criteria v 4.0), the same dose was continued. If response was suboptimal and adverse events were grade 2 or better, the dose was increased by 20 mg/day. Once a dose reduction had been made because of a grade 3 or worse adverse event, there were no further dose increases. Treatment was discontinued if assessed as failure (disease progression to the accelerated phase or acute phase). The primary endpoint was the achievement of major molecular response at 12 months, assessed using a per-protocol analysis. This trial is registered at with the UMIN clinical trial registry, UMIN000024548, and has completed its planned observation period. Findings: Between Nov 1, 2016, and Oct 30, 2019, 52 patients received first-line dasatinib therapy at 20 mg/day. The median age at diagnosis was 77·5 years (73·5–83·0). 35 (67%) patients were male and 17 (33%) were female. 31 (60%) of 52 patients reached major molecular response at 12 months (one-sided 95% CI 48–71), with a median follow-up of 366 days (IQR 353–372). Grade 3–4 adverse events were reported in 12 (23%) patients. Neutropenia was the most frequent grade 3–4 adverse event, occurring in three (6%) patients. No treatment-related deaths were observed. Interpretation: Low-dose dasatinib at 20mg/day is worthy of consideration as a starting dose for older patients with newly diagnosed chronic myeloid leukaemia in the chronic phase. However, this dose needs to be further studied in a larger cohort and with a more ethnically diverse population. Funding: Bristol-Myers Squibb.